Analisis Model Pembelajaran Guided Discovery Learning Berbasis Video Pembelajaran terhadap Kemampuan Pemecahan Masalah Siswa SMA Negeri di Kota Yogyakarta: Bahasa Indonesia - Aruna Akbar Zhafransyah; Suyanta Suyanta; Dea Nanda Sari (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyze the profile of students' problem-solving abilities taught using the guided discovery learning model. This model involves a process in which students discover new knowledge, which ideally should be facilitated by teachers who provide initial guidance to create new knowledge from the teacher's existing knowledge and students' active experiences. Thus, the Guided Discovery Learning learning model is believed to be able to improve students' cognitive abilities, one of which is problem-solving ability. The indicators of the problem-solving ability profile used in this study are formulating problems, formulating hypotheses, testing hypotheses, and conclusions. The sample in this study was 72 students at a public school in Yogyakarta that was accredited A in the odd semester of the 2023/2024 academic year. This study uses quantitative descriptive. Students are first given chemical bonding material taught using the Guided Discovery Learning learning model with video learning media. After that, data collection was carried out through posttest questions consisting of 10 descriptive questions on the chemical bonding material. The results of the study stated that the indicators of students' problem-solving abilities were very high. Meanwhile, the indicators for formulating students' hypotheses were in the high category. Meanwhile, the indicators of hypothesis testing and student conclusion formulation are in the sufficient category. This study concludes that the profile of students' problem-solving abilities is in the sufficient category of 38.9%.